Missense and nonsense mutations in the lysosomal alpha-mannosidase gene (MANB) in severe and mild forms of alpha-mannosidosis. - Gotoda, Y (1998)
alpha-Mannosidosis is an autosomal recessive lysosomal-storage disorder caused by a deficiency of lysosomal alpha-mannosidase activity. This disease shows a wide range of clinical phenotypes, from a severe, infantile form (type I), which is fatal at <3-8 years of age, to a less severe, late-onset form (type II), which ultimately may involve hearing loss, coarse face, mental retardation, and hepatosplenomegaly. To elucidate the molecular mechanism underlying this disease in both types of patients, we have used PCR, followed by either SSCP analysis or direct sequencing, to analyze the 24 exons and intron/exon boundaries of the alpha-mannosidase gene (MANB) from five patients. Two amino acid substitutions-H72L and R750W, in exons 2 and 18, respectively-and two nonsense mutations-Q639X and R760X, in exons 15 and 19, respectively-were identified in four type II patients. One amino acid substitution, P356R, was identified in exon 8 from a type I patient. This patient and three of the type II patients were homozygous for their mutations (H72L, P356R, R750W, and R760X) and one type II patient was heterozygous for the Q639X and R750W mutations. Transfection experiments of COS 7 cells, using the alpha-mannosidase cDNA containing one of the missense mutations-H72L, P356R, or R750W-revealed that each of these mutations dramatically reduces the enzymatic activity of alpha-mannosidase. These data demonstrate that widely heterogeneous missense or nonsense mutations of the MANB gene are the molecular basis underlying alpha-mannosidosis.